2009
DOI: 10.1002/ibd.20914
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive total proctocolectomy with Brooke ileostomy for ulcerative colitis

Abstract: Minimally invasive total proctocolectomy with Brooke ileostomy is a safe, feasible option for the surgical treatment of chronic ulcerative colitis, and is the procedure of choice for select patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
2
15
1
Order By: Relevance
“…The overall postoperative morbidity rate of 39.7% reported in the present study falls within the 16-60% range reported from current laparoscopic TAC series (Table 4) and is also consistent with the 40.1% morbidity reported in a review of pooled data from the past decade [4]. This wide variability in reported complications depends at least in part on the definitions of morbidity and patient case mix, which limits the value of interstudy comparisons [9][10][11]13,14]. The reported morbidity in the present study has several characteristics.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The overall postoperative morbidity rate of 39.7% reported in the present study falls within the 16-60% range reported from current laparoscopic TAC series (Table 4) and is also consistent with the 40.1% morbidity reported in a review of pooled data from the past decade [4]. This wide variability in reported complications depends at least in part on the definitions of morbidity and patient case mix, which limits the value of interstudy comparisons [9][10][11]13,14]. The reported morbidity in the present study has several characteristics.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of individual complications is similar to that reported by others ( Table 4). The 15% incidence of distal stump leakage is in sharp contrast with the current literature on laparoscopic TAC, in which it has been either reported sporadically [11,12] or more often not at all [5,[7][8][9][10][13][14][15]27], including in the initial report from our own institution [6]. The complication rate was reported in a systemic review to be 6.7% after open TAC and a rate as high as 35% was reported after subcutaneous stump placement even in a tertiary institution [4,28].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition to the conventional access for these resections, laparoscopic procedures are available that reduce invasiveness. The laparoscopic approach was first described by Jacobs et al in 1991 andFranklin et al in 1993 [5, 6] and has since become a standard access [7][8][9][10]. Laparoscopic-assisted resection (LAR) requires an additional incision to remove the resected specimen, while total laparoscopic resection (LR) further reduces the access trauma [11][12][13].…”
mentioning
confidence: 99%